(untitled) (International Journal of Engineering & Extended Technologies Research (IJEETR), 2026)
Man-Machine Interface (MMI) has emerged as a significant research area aimed at improving the quality of life for differently-abled individuals. This paper presents the design and development of a mechatronic system that enables disabled users to control assistive devices using Electrooculography (EOG) signals generated through eye blinks. Traditional assistive technologies often lack affordability, usability, and real-time performance in practical environments. The proposed system utilizes a single-channel EOG-based interface to detect voluntary eye blinks and convert them into control commands. A threshold-based algorithm is implemented for signal processing and command generation. The system is further integrated with a motorized wheelchair, enabling users to navigate independently without the need for muscular movement. Experimental results demonstrate that the system provides reliable performance with improved accuracy, faster response time, and user-friendly operation. The proposed system offers a cost-effective, robust, and practical solution for assisting disabled and elderly individuals, thereby enhancing independence and mobility